2011
DOI: 10.1097/cad.0b013e328345b509
|View full text |Cite
|
Sign up to set email alerts
|

Randomized phase II trial of first-line treatment with tailored irinotecan and S-1 therapy versus S-1 monotherapy for advanced or recurrent gastric carcinoma (JFMC31-0301)

Abstract: Objective: The pharmacokinetics of irinotecan vary markedly between individuals. This study sought to compare tailored irinotecan plus S-1 therapy with S-1 monotherapy for the treatment of patients with advanced/recurrent gastric cancer. Methods:Patients with advanced/recurrent gastric cancer were randomized to receive tailored irinotecan plus S-1 (arm A) or S-1 alone (arm B). Arm A received S-1 (80−120 mg/m 2 /day) for 14 days, with irinotecan on days 1 and 15. The initial irinotecan dose of 75 mg/m 2 (Level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…With regard to the chemotherapy used, the combined regimens of irinotecan differed between included studies; however, all studies used irinotecan-based doublet therapy, and combined drugs included docetaxel, 25 cisplatin, 22,39 oxaliplatin, 28 S-1 23,24,27 or 5-FU. 26,37,38 In addition, the controlled groups in trials were also different; three trials [22][23][24] used monotherapy as controlled group, whereas the others [25][26][27][28][37][38][39] used combination therapy as controlled group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…With regard to the chemotherapy used, the combined regimens of irinotecan differed between included studies; however, all studies used irinotecan-based doublet therapy, and combined drugs included docetaxel, 25 cisplatin, 22,39 oxaliplatin, 28 S-1 23,24,27 or 5-FU. 26,37,38 In addition, the controlled groups in trials were also different; three trials [22][23][24] used monotherapy as controlled group, whereas the others [25][26][27][28][37][38][39] used combination therapy as controlled group.…”
Section: Discussionmentioning
confidence: 99%
“…26,37,38 In addition, the controlled groups in trials were also different; three trials [22][23][24] used monotherapy as controlled group, whereas the others [25][26][27][28][37][38][39] used combination therapy as controlled group. Therefore, we did subgroup analysis based on the controlled therapy and found that for each of these patient subsets, irinotecan-containing chemotherapy had slightly better efficacy than monotherapy (HR ¼ 0.88, 95% CI ¼ 0.77-1.00) or nonirinotecan-containing combination therapy (HR ¼ 0.83, 95% CI ¼ 0.71-0.96).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S-1 is a 1:0.4:1 molar ratio mixture of tegafur and 2 5-FU-modulating substances: gimeracil (5-chloro-2, 4-dihydroxy-pyrimidine) and oteracil (potassium oxonate) [5]. The RR of S-1 as a single agent was promising at around 32% in gastric cancer [6,7,8]. In the FLAGS trial, S-1 demonstrated a similar efficacy and better toxicity profile compared to infusional 5-FU.…”
Section: Introductionmentioning
confidence: 99%